R. Hunter, Theocritus and the Archaeology of Greek Poetry, Cambridge University Press, 1996, XII + 207 pp. (Minerva, 2019)
Review: R. Hunter, Theocritus and the Archaeology of Greek Poetry, Cambridge University Press, 1996, XII + 207 pp.